Long-term results of decompression and muscle-pedicle bone grafting for osteonecrosis of the femoral head - Baksi, Durgapada P. (Springer-Verlag, 2007)
In this paper, 152 patients with 187 osteonecrotic femoral heads (83 idiopathic, 56 corticosteroid induced, 40 post-traumatic, seven alcohol abuse and one associated with gout) were classified according to the staging by Ficat and Arlet (Ischemia and necroses of bone, Williams and Wilkins, Baltimore, Maryland, pp 171–182, 1980); four were in Stage I, 82 in Stage II and 101 in Stage III. The majority of the patients were young (average age 35.5 years). Multiple drilling, curettage of the necrotic bone and muscle-pedicle bone grafting using tensor fascia lata was carried out in all patients except in six adolescents, where sartorius grafting was performed. Cheilectomy of the femoral head and subcutaneous adductor tenotomy were also performed in the advanced stages. During the follow up of 10 to 21.5 years (average 16.5 years), radiological improvement was noted in 81.3% of patients in Stage II and 70.1% of patients in Stage III cases. Excellent and good results according to the Hospital for Special Surgery (HSS) score were obtained in 100% of cases in Stage I, 92% in Stage II and 80.4% in stage III, with a survivorship of 91% in Stage II and 82% in Stage III cases. The patients having an HSS score below 20 (non-survival) were recommended for total hip replacement (THR) therapy.